Правові засади інфраструктурного забезпечення інноваційного процесу - Подрез-Ряполова, І. В. (НДІ ПЗІР НАПрН України, 2022)
У науковій роботі досліджені правові засади інфраструктурного забезпечення інноваційного процесу. Встановлено, що ефективна інноваційна діяльність та комерціалізація її результатів можлива лише за умови належного організаційного та інформаційно-посередницького інфраструктурного забезпечення інноваційного процесу. Визначено, що сучасна українська держава має дуже обмежену фінансову та інституційну спроможність, відтак наявні ресурси і потенціал доцільно зосередити на підтримці наукових досліджень, які є однією з основ інноваційного потенціалу, та створенні ефективної інфраструктури, яка сприятиме перетворенню результатів досліджень у продукт, придатний до комерціалізації. Зроблений аналіз чинних нормативно-правових актів та документів стратегічного планування, які регламентують питання інфраструктурного забезпечення інноваційного розвитку економіки. Так, проаналізовані положення Закону України «Про інноваційну діяльність», Стратегії розвитку сфери інноваційної діяльності на період до 2030 року, Державної цільової програми розвитку системи інформаційно-аналітичного забезпечення реалізації державної інноваційної політики та моніторингу стану інноваційного розвитку економіки, Стратегії розвитку інформаційного суспільства в Україні, Стратегії інформаційної безпеки. Зокрема, проаналізовані положення Стратегії інформаційної безпеки, передбачають необхідність стимулювання інновацій та забезпечення всебічного розвитку й захисту національної інформаційної інфраструктури, зокрема її телекомунікаційної складової, як сукупності різноманітних інформаційних систем, інформаційних ресурсів, телекомунікаційних мереж, засобів комунікацій і управління інформаційними потоками, а також організаційно-технічних структур, механізмів, що забезпечують їх функціонування. Втім питання інформаційного забезпечення інноваційної діяльності недостатньо регламентовані більшістю проаналізованих стратегічних документів. У роботі досліджені окремі проблемні питання та запропоновані шляхи вдосконалення організаційного та інформаційно-посередницького забезпечення інноваційного процесу. Problem setting. Effective innovation activity and commercialization of its results is possible only with proper organizational and information-intermediary infrastructure support of the innovation process. The problem of creating a system of information and analytical support of scientific, technical and innovative activities in Ukraine in the formation of an innovative model of economy, which provides for a sustainable flow of effective innovation and transition of the entire domestic economy to knowledge-intensive technologies, is urgent and requires fundamentally new approaches to its development communication through the use of advanced information technology Target of research. The purpose of this study is to analyze the legal basis of infrastructure support of the innovation process. Analysis of recent researches and publications. The research of many scientists is devoted to the organization of the innovation process, development of innovation infrastructure, intensification of innovation activities and commercialization of its results. Thus, S.V. Hlibko considered modern requirements for the development of the national innovation system, organizational and legal forms and functions of certain subjects of innovation. Problematic issues regarding organizational forms of technology transfer in the innovation process were analyzed in the studies of O.V. Rozghon. Iu. V. Georgiievskyi studied the features of public administration of the national innovation system of Ukraine from the standpoint of structural and functional approach. In addition, A. N. Liubchych assessed the activities of technology parks and determined their role in the national innovation system. However, insufficient attention is paid to the problems of infrastructural support of the innovation process, which actualizes these issues. Article’s main body. Today, the organizational support of innovation and the intermediary component of information support are left out of consideration. It should be noted that information support of innovation can be considered as a set of legal, timely, effective, purposeful and secure processes of collection, perception, storage, processing, transmission, provision, receipt and use of relevant information to solve problems of legal regulation of innovation .It should be agreed that today there are ample opportunities for the emergence of new types of intermediaries that provide infrastructure for modern business models, while further efforts should be focused on researching intermediaries in the market of information and information products, so information requires significant efforts its collection, processing and storage, which creates ample opportunities for intermediary enterprises, but also requires consideration of the characteristics of the information product. Conclusions and prospects for the development. Issues of legal support of the innovation process are extremely relevant and require scientific disclosure. Thus, given the importance of building a national innovation ecosystem and infrastructure support of the innovation process, it is appropriate at the present stage of development to improve the regulatory framework for organizational and information-mediation infrastructure support of innovation, legislative regulation of innovation market intermediaries, monitoring of information resources and information resources, communication networks among research institutions in order to promote effective innovation and commercialization of its results.
Keywords: інноваційна діяльність; інноваційний розвиток; інноваційний процес; інфраструктурне забезпечення; інформаційні технології; innovation activity; innovation development; innovation process; infrastructure provision; information technologies